Agri-energy chains: from field to land planning - Massimo Monteleone; Salvatore Luciano Cosentino; Giuseppe De Mastro; Marco Mazzoncini (Italian Journal of Agronomy)
A general consensus on bio-energy and renewable energetic sources is expressed by modern societies; at the same time, some concerns and uncertainties are related to the actual ecological and environmental standards that these new technologies are able to fulfill. The overall energy demand is permanently rising as the economic growth spread through new developing countries. The consciousness about the limited petroleum availability and the negative environmental consequences related to fossil fuels exploitation, inevitably calls for a new global energy model based on a drastic improvement on energy use efficiency, energy savings and renewables. On this respect, biomass could play an important role to meet these new constraints and requirements. The development of bio-energy needs a reliable biomass availability, a well organized and integrated chain-supply and reasonable costs of the biomass feedstock in order to be competitive with respect to conventional fossil-fuels. Different productive and distributive chain-supply can be depicted, at the large as well as at the local-scale; pros and cons can be identified for both, but locally produced bio-energy and “distributed” energy generation is mostly favored by general society and some stakeholders; it seems to better support landowners, rural economy and local market; at the same time, the environmental benefits seems to be higher. Rigorous evaluation procedures, such as “Life Cycle Assessment”, must be ordinarily implemented to proper compare such alternatives with each other and choose the one that fits better.